Kebijakan Perizinan Sesuai Asas Diskresi Terkait Manajemen Risiko dalam Perspektif Negara Hukum Kesejahteraan - Sarira, Iron (Humaniora, 2011)
As a country that respects the rule of law, permission can be a commodity as the establishment of a policy creation rules or derivation of state law dogma. The subject of law could not be carelessly with the presence of policies and regulations. The application of risk management as a restraint order in respect of the manufacture of the permits to the safety and health of work object (K3) which consists of main and ancillary infrastructure the production process on the company or the bureaucracy, making the value of the uncertainty (uncertainty) associated risks that occur can be deduced that in turn would provide welfare (welfare) from persons per person on the micro level to the contry?s macro level. The law in respect of the implementation of the licensing on this writing more leads to the existence of risk in the field of safety and Health (K3) as a measurement of the success of the control pattern related to risk management application in the company.